Oddajni sistemi: laboratorijske vaje - Donaj, Gregor; Kramberger, Iztok (2019)
Broadcast systems: laboratory exsecises. This material contains the instructions for laboratory work in the subject  Broadcast systems for students of the university study program Telecommunications. The instructions contain ten laboratory exercises. The first two exercises cover the laboratory measurement equipment, which will be used in later exercises. The next four exercises deal with analog amplitude and frequency modulations as well as their use in audio broadcast systems. The last four exercises deal with digital modulations and multiplexing as well as the use of those technologies in DVB-T terrestrial television systems.
Keywords: telecomunications; lavboratory work; measurment equipment; analog modulations; digital modulations; digital television